The Relationship between Demographic Characteristics and Nutritional Status on Anemia among Balinese Traditional Porter after the COVID-19 Pandemic - Putu Ratna Suprima Dewi; Ni Putu Ayu Wulan Noviyanti; I Kadek Agus Dwija Putra; Yupin Aungsuroch (Babali Nursing Research, 2023)
Introduction: The impact of the pandemic on people's lives, one of which is a decrease in income. Wanita tukang suun who earned income depends on the needs of customers in the market in using their services. Limited income makes it difficult for them to provide nutritious food, this makes them vulnerable to experienced is anemia. This study aims to determine the relationship between daily income, age, marital status and nutritional status with anemia in wanita tukang suun in the Badung Market Heritage Area after the Covid-19 pandemic. Methods: This study used a cross sectional research design. The sample in this study was selected by total sampling so as to obtain 107 wanita tukang suun who work in the Badung Market Heritage Area as respondents. The inclusion criteria in this study were wanita tukang suun who were over 18 years old and used a basket as transportation tools. Research data were collected using several validated and calibrated instruments. Result: The results of the univariat analysis showed mostly wanita tukang suun had daily income more than IDR 50.000 (70,1%), aged more than 45 years (80,4%), had married (89,7%), had normal nutritional status (52,3%) and had mild anemia (86,0%). Then bivariate analysis showed that the variables of daily income (p value = 0357), age (p value = 0459) and marital status (value 0.619), where p value <0.05 and the nutritional status variable (p value = 0.021), where the p value <0.05. Conclusion: This study showed that there is no significant relationship with the incidence of anemia among wanita tukang suun. Different results were obtained on the nutritional status variable has significant relationship between nutritional status and anemia among wanita tukang suun.